2014
DOI: 10.1155/2014/123581
|View full text |Cite
|
Sign up to set email alerts
|

A New Measure of Decompression Sickness in the Rat

Abstract: In this study we assessed the reliability of a tilting-board grip score as a measure of decompression sickness in rats. In experiments using a hyperbaric compression/decompression protocol, rats were observed for signs of decompression sickness and their grip strength measured on a tilting particle board hinged to a metal frame. Angles at which rats lost grip were converted to gravitational vectors. Decreased mean grip scores following decompression were fitted to a logistic regression model with strain, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Again, an appropriate weighting for sDCS may have an appreciable effect upon this test. Overall, the relationship between DCS and weight, sex and strain have all been experimentally confirmed in our laboratory, 23,38 and the relationship between DCS and Max1, Max1b and Bubble3 are in accord with what is known of DCS, namely that ascent rate and supersaturation are key factors, and that saturation in the rat occurs at around 60-90 mins.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Again, an appropriate weighting for sDCS may have an appreciable effect upon this test. Overall, the relationship between DCS and weight, sex and strain have all been experimentally confirmed in our laboratory, 23,38 and the relationship between DCS and Max1, Max1b and Bubble3 are in accord with what is known of DCS, namely that ascent rate and supersaturation are key factors, and that saturation in the rat occurs at around 60-90 mins.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, we experimentally confirmed that DCS incidence in this compression/decompression profile elicited similar incidence of DCS between Wistar and Sprague-Dawely. 23 This should be reassuring to the scientific community who rely on previous research utilising either one strain or the other. That exercise was not significant may be explained by the inclusion criteria that at least one rat must be represented in each outcome state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using an ED-50 rat model have classified their outcome variables as DCS vs. No-DCS, whereby the marginal cases were combined with the dead, or the classification was Dead vs. Not-Dead, where the marginal cases were combined with the asymptomatic. In this study the ternary classification of “No DCS” (no symptoms), mild “DCS” (with at least one symptoms excluding death within the observation period) or severe DCS (“Death” within 1 h) was retained to maximize statistical power, as described by Buzzacott et al ( 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…DCS was diagnosed by three observers who were unaware of the treatment. According to the evaluation criteria of decompression sickness 23 , 24 , the rats were diagnosed as DCS if any one of the symptoms of scratching, sluggishness, tachypnea or dyspnea, cyanosis, paralysis, convulsions, and death occurred after treatment. Severe DCS was defined as having at least one symptom, including paralysis, dyspnea, convulsions, and death.…”
Section: Methodsmentioning
confidence: 99%